Asuhan Keperawatan melalui Pemberian Sari Kacang Hijau pada Ny.F dengan Diagnosis Anemia dalam Kehamilan di Desa Mandikapau Timur - Miftakhul Jannah; Pertiwiwati, Endang (Nerspedia, 2023)
High-risk pregnancy is a pregnancy that will cause greater danger and complications to the mother and during pregnancy. The anemia rate in Indonesia according to the Ministry of Health in 2018 was 48.9% of pregnant women in Indonesia experienced anemia. To determine the results of nursing care ineffective peripheral tissue perfusion with the etiology of decreasing the concentration of hb through the administration of green bean juice. The intervention of mung bean juice in the morning/afternoon for 7 days with a pre post test design approach.